2020
DOI: 10.1002/eom2.12055
|View full text |Cite
|
Sign up to set email alerts
|

Design strategies for organic carbonyl materials for energy storage: Small molecules, oligomers, polymers and supramolecular structures

Abstract: Organic electrodes are attractive candidates for electrochemical energy storage devices because they are lightweight, inexpensive and environmentally friendly. In recent years, many researchers have focused on the development of carbonyl-containing materials for organic electrodes. These materials demonstrate promising results as the next generation of rechargeable batteries owing to their fast redox kinetics and structural diversity in design. However, these electrodes still exhibit intrinsic drawbacks such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 99 publications
(227 reference statements)
0
23
0
Order By: Relevance
“…[ 10,11 ] Among all organic electroactive anode materials, carbonyl (CO) group‐based compounds are being explored as the main candidates for LIBs owing to their high theoretical capacity, accessible active sites, easy synthesis, and availability from natural resources. [ 12–14 ] In particular, cyclohexanehexone (C 6 O 6 ), as a perfect structure composed entirely of six CO groups, can theoretically contribute the largest number of reactive sites and the highest specific capacity when used as an anode material. However, the research of C 6 O 6 as the anode material for LIBs has not been reported yet so far, which may be attributed to two key bottlenecks: the high solubility in the traditional carbonate‐based electrolytes and extremely low intrinsic electronic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10,11 ] Among all organic electroactive anode materials, carbonyl (CO) group‐based compounds are being explored as the main candidates for LIBs owing to their high theoretical capacity, accessible active sites, easy synthesis, and availability from natural resources. [ 12–14 ] In particular, cyclohexanehexone (C 6 O 6 ), as a perfect structure composed entirely of six CO groups, can theoretically contribute the largest number of reactive sites and the highest specific capacity when used as an anode material. However, the research of C 6 O 6 as the anode material for LIBs has not been reported yet so far, which may be attributed to two key bottlenecks: the high solubility in the traditional carbonate‐based electrolytes and extremely low intrinsic electronic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Organic electrode materials are attractive candidates for electrochemical energy storage devices because they are naturally abundant, relatively inexpensive, produce minimal waste when recycled, have high specific capacities, and can exhibit long cycling stability 1–3 . Among the many redox‐active organic compounds, carbonyl compounds, in particular, have emerged as one of the most promising cathode materials for lithium‐ion batteries (LIB) 4,5 . Carbonyl compounds have tailorable structures and properties, and well‐known redox chemistry, which can enable high gravimetric energy density and high specific capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Alkali metal batteries, especially lithium‐ion batteries have been widely applied as electrochemical energy storage devices attributed to their renewability, safety, and cyclic stability 6–8 . However, the energy density is restricted by low theoretical capacity of the traditional graphite anode 9,10 . Alloy anode materials (e.g., Si, Al, Sn, Zn, Bi, and Sb) which can be alloyed with reactive ions (e.g., Li + , Na + , Ca 2+ , or K + ) are considered to be promising anode for the next generation electrochemical energy storage devices due to their high theoretical capacity 11–15 .…”
Section: Introductionmentioning
confidence: 99%